2009
DOI: 10.1038/ni.1766
|View full text |Cite
|
Sign up to set email alerts
|

Themis controls thymocyte selection through regulation of T cell antigen receptor–mediated signaling

Abstract: Themis (Thymocyte expressed molecule involved in selection), a member of a family of proteins with unknown functions, is highly conserved among vertebrates. Here we found that Themis is expressed in high amounts in thymocytes between the pre-T cell receptor (TCR) and positive selection checkpoints, and in low amounts in mature T cells. Themis-deficient thymocytes exhibit defective positive selection, which results in reduced numbers of mature thymocytes. Negative selection is also impaired in Themis-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
177
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(202 citation statements)
references
References 44 publications
17
177
1
2
Order By: Relevance
“…Despite the absence of strong biochemical evidence, it was presumed that Themis1 likely functions as a positive regulator of TCR signaling because several defects in Themis1 −/− mice, such as a marked impairment of both positive and negative selection, were consistent with a deficiency in TCR signaling (2)(3)(4)(5)(6). It was subsequently shown that Themis1 interacts with Vav1 and that Vav1 phosphorylation is reduced in Themis1 −/− thymocytes, results that also implied a positive role for Themis1 in TCR signaling (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the absence of strong biochemical evidence, it was presumed that Themis1 likely functions as a positive regulator of TCR signaling because several defects in Themis1 −/− mice, such as a marked impairment of both positive and negative selection, were consistent with a deficiency in TCR signaling (2)(3)(4)(5)(6). It was subsequently shown that Themis1 interacts with Vav1 and that Vav1 phosphorylation is reduced in Themis1 −/− thymocytes, results that also implied a positive role for Themis1 in TCR signaling (9).…”
Section: Discussionmentioning
confidence: 99%
“…We and others identified the previously uncharacterized protein Themis1 as being required for the positive selection and maturation of T cells in the thymus (2)(3)(4)(5)(6). Themis1 lacks any discernable catalytic domain, but it contains two previously uncharacterized cysteine-based globular domains (named "CABIT") of unknown structure and function (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to note that, during the review process of this article, several other groups' reports describing the same gene under the name "Themis" were published (33)(34)(35)40).…”
Section: Discussionmentioning
confidence: 99%
“…THEMIS expression is limited to lymphoid tissues, and studies in mice have shown that it encodes an important molecule for T-cell development, being expressed at higher levels in pre-TcR thymocytes. 5 Although its expression is reduced in differentiated T lymphocytes, 6 it is thought to have a role in TcR activation signaling. 7 In turn, PTPRK performs functions related to the maintenance of cell junctions [8][9][10] and in the modulation of epidermal growth factor receptor (EGFR) activity, resulting in an inhibition of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%